Enhancement of intergranular corrosion resistance of type 304 stainless steel through laser shock peening. (3rd April 2017) - Gupta, R. K.; Sunil Kumar, B.; Sundar, R.; Ram Sankar, P.; Ganesh, P.; Kaul, R.; Kain, V.; Ranganathan, K.; Bindra, K. S.; Singh, B.
ABSTRACT: The present experimental study evaluates laser peening for suppressing intergranular corrosion (IGC) susceptibility of sensitised 304 stainless steel. Under the given experimental conditions, an increase in the number of laser peening treatments of sensitised 304 stainless steel specimen brought about progressive reduction in its susceptibility to IGC. Triple laser peening of sensitised stainless steel specimen introduced remarkable reduction in its IGC susceptibility. The results of the study suggest that breakage of inter-granular network of chromium carbides/chromium-depleted regions through plastic deformation, imposed by multiple laser peening treatment, was responsible for causing significant suppression in IGC susceptibility of sensitised 304 stainless steel specimens.